Pelatihan Simulasi Robot Inline Untuk Peningkatan Ketrampilan Teknologi Di SMK 10 Nopember Jakarta Selatan - Widayat, Puspita Dewi; Ariyanti, Silvi (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
The inline robot simulation training at SMK 10 Nopember, South Jakarta, aims to enhance students' technological skills and digital literacy to meet modern industry demands. The rapid development of information technology, including robotics, requires vocational schools to update their competencies. Limited access to basic robotics knowledge poses a significant challenge. This community service program includes simulation-based training that replicates real industrial conditions. Teachers also gain innovative teaching enrichment. The Industrial Engineering Department of Universitas Mercu Buana provides educational support through knowledge transfer. The training focuses on understanding and evaluating the inline robot simulation in digital industries. Expected outcomes include improved student understanding, academic publications, video documentation, and media articles. This program is designed to strengthen SMK graduates' competitiveness with industry-relevant skills.